The Role Of Nitric Oxide On The Proliferation Of Human Osteoblasts (Hos Cells) Stimulated With Hydroxyapatite - Sugiatno, Erwan (2006)
Hydroxyapatite (HA) as a ceramic material is widely used for orthopaedic and dental implants, since this biomaterial has ability to stimulate osteoblast functions in vitro and in vivo. However, the exact mechanism by which HA accelerates osteoblast function, thereby stimulating rapid bone formation, remains far from clear. It is well known that bone formation is tightly regulated by nitric oxide (NO) via its effects on osteoblast and osteoclast function. Therefore, the overall aim of the present studies was to elucidate the possible regulation ofNO in HA-stimulated HOS cell proliferation. The present study used a human osteoblast cell line (HOS cells), since this cell line is known to mimic the functions of normal human osteoblasts, thereby representing the biological response of normal osteoblasts in humans. Hidroksiapatit (HA), yang merupakan bahan seramik, digunakan dengan meluas didalam bidang ortopedik dan implantologi pergigian kerana keupayaannya untuk meyebabkan stimulasi fungsi 'in vitro' dan 'in vivo' sel osteoblas. Walaubagaimanapun, mekanisma dimana HA menggalakkan fungsi sel osteoblas, iaitu pembentukkan tulang masih tidak jelas. Nitrik oksida (NO) meregulasi pembentukkan tulang melalui kesannya terhadap fungsi sel osteoblas dan osteoklas. Maka, tujuan keseluruhan kajian terkini adalah untuk mengetahui kemungkina:n regulasi NO tethadap proliferasi sel HOS yang telah distimulasi oleh HA. Kajian ini telah meggunakan sel induk osteoblas manusia (sel HOS) kerana sel-sel ini dapat mewakili respons biologikal sel osteoblas normal manusia.